Managing Science Methodology and Organization of Research - Betz, Frederick; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
What is science? How is it performed? Is science only a method or is it also an institution? These are questions at the core of Managing Science, a comprehensive handbook on how scientific research is and should be conducted and its results disseminated.Knowledge creation occurs through scientific research in universities, industrial laboratories, and government agencies. Any knowledge management system needs to promote effective research processes to foster innovation, and, ultimately, to channel that innovation into economic competitiveness and wealth. However, science is a complicated topic. It includes both methodological aspects and organizational aspects, which have traditionally been discussed in isolation from each other. In Managing Science, Frederick Betz presents a holistic approach to science, incorporating both philosophical and practical elements, in a framework that integrates scientific method, content, administration and application. Illustrating all of the key concepts with case studies (both historical and contemporary, and from a wide spectrum of fields), Betz provides in-depth discussion of the process of science. He addresses the social, organizational, institutional, and infrastructural context through which research projects are designed and performed, and their results applied, along the path from science to technology to economy. This theoretical and practical approach to science is the foundation of today's knowledge-intensive and technology-enabled industries, and positions the management of science within the broader context of knowledge management and its implications for organizations, industries, and regional and national technology management policies. Managing Science will be an essential resource for graduate students in all areas of research, professors submitting research proposals and performing research grants, industry scientists, R&D specialists, research policymakers and university administrators, and anyone fascinated with science in the discovery and application of knowledge.
Keywords: Economics; Economics -- Methodology; Economics/Management Science; R & D/Technology Policy; Methodology and the History of Economic Thought; Innovation/Technology Management